2020
DOI: 10.1186/s12883-020-01924-9
|View full text |Cite
|
Sign up to set email alerts
|

The misdiagnosis of prolonged disorders of consciousness by a clinical consensus compared with repeated coma-recovery scale-revised assessment

Abstract: Background Previous studies have shown that a single Coma-Recovery Scale-Revision (CRS-R) assessment can identify high rates of misdiagnosis by clinical consensus. The aim of this study was to investigate the proportion of misdiagnosis by clinical consensus compared to repeated behavior-scale assessments in patients with prolonged disorders of consciousness (DOC). Methods Patients with prolonged DOC during hospitalization were screened by clinicians, and the clinicians formed a clinical-consensus diagnosis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…Many studies have shown that the fluctuations of MCS often leads to missed diagnosis (the missed diagnosis rate may be higher than 35%) (Stender et al, 2014 , van Erp et al, 2015 ), and that such diagnostic errors can affect patient outcomes and treatment decisions (Demertzi et al, 2011 ). Especially when DOC patients were tested only once, even when using the most sensitive scale of the Coma Recovery Scale-Revised (CRS-R) (Giacino et al, 2004 ), a single assessment resulted in a 25% missed diagnosis (Wang et al, 2020 ). Therefore, recent guidelines have emphasized the importance of repeated assessments to increase the accuracy of clinical diagnosis (Giacino et al, 2018 ; Kondziella et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the fluctuations of MCS often leads to missed diagnosis (the missed diagnosis rate may be higher than 35%) (Stender et al, 2014 , van Erp et al, 2015 ), and that such diagnostic errors can affect patient outcomes and treatment decisions (Demertzi et al, 2011 ). Especially when DOC patients were tested only once, even when using the most sensitive scale of the Coma Recovery Scale-Revised (CRS-R) (Giacino et al, 2004 ), a single assessment resulted in a 25% missed diagnosis (Wang et al, 2020 ). Therefore, recent guidelines have emphasized the importance of repeated assessments to increase the accuracy of clinical diagnosis (Giacino et al, 2018 ; Kondziella et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also true that these scales are not sensitive to covert changes in cognitive functioning or awareness ( 73 ). On the one hand, clinical scales mainly rely on motor outputs, which can be highly inconsistent and limited in PDOC, due to lesions in motor cortices ( 15 , 39 , 74 , 75 ). In addition, the presence of injury in language and visual cortices may also interfere with the patients' ability to understand the instructions and show appropriate responses ( 76 ).…”
Section: Common Methodological Limitationsmentioning
confidence: 99%
“…Given that patients with prolonged disorders of consciousness are often misdiagnosed ( Wang et al, 2020 ), beyond CLIS, there is critical need for robust non-invasive bed-side tools to evaluate level of consciousness and for re-establishing communication. Besides their immediate impact on self-determination and quality of life, such systems may also trigger neural recovery as it was shown for BCIs in restoration of movement and accelerate emergence from minimally conscious state (EMCS).…”
Section: Optical Brain Imaging and Its Application To Neurofeedbackmentioning
confidence: 99%